Hexaaquazinc(II) dipicrate - Natarajan, S. (International Union of Crystallography, 2008)
In the title compound, [Zn(H(2)O)(6)](C(6)H(2)N(3)O(7))(2), the Zn(II) ion is located on an inversion center and is coordinated by six water molecules in an octahedral geometry. The picrate anions have no coordination interactions with the Zn(II) atom. The three nitro groups are twisted away from the attached benzene ring by19.8 (3), 6.5 (4) and 28.6 (3)°. There are numerous O—H⋯O hydrogen bonds in the crystal structure.